2009
DOI: 10.1007/s12206-009-0924-0
|View full text |Cite
|
Sign up to set email alerts
|

Linear stability analysis of acoustically driven pressure oscillations in a lean premixed gas turbine combustor

Abstract: The dynamic response of a turbulent premixed flame to acoustic velocity perturbations was experimentally determined in a swirl-stabilized lean-premixed gas turbine combustor. CH* chemiluminescence intensity and the twomicrophone method were used to measure heat release rates and inlet velocity fluctuations, respectively. Using the n-τ formulation, gain and phase of flame transfer functions were incorporated into an analytic thermoacoustic model to predict instability frequencies and modal structures. Self-exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…On the element level one may be interested in the acoustical response of an unflanged open end [8], or the acoustical response of a flame [2]. Finally, there is a wealth of literature on the analysis of thermoacoustic systems on a complete system level, see for example the various linear and nonlinear studies in [3,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…On the element level one may be interested in the acoustical response of an unflanged open end [8], or the acoustical response of a flame [2]. Finally, there is a wealth of literature on the analysis of thermoacoustic systems on a complete system level, see for example the various linear and nonlinear studies in [3,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In most of cases, combustion stabilization is not attained over a full range of operating conditions, but limited to only a certain range of conditions, e.g., specific fuel and oxidizer mass flows [6,7], specific inlet fuel and oxidizer temperatures [8], specific chamber outlet boundary conditions [9], and specific fuels [8,[10][11][12]. In practice, fuel and oxidizer mass flows are increased to produce high power output.…”
Section: Introductionmentioning
confidence: 99%
“…In the former, the instability occurs spontaneously without external perturbation [15,16]. On the other hand, forced instability is triggered by perturbation [7,17]. A gas-centered swirl coaxial (GCSC) injector has been adopted widely in high-performance rocket engines, especially, with a staged combustion cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Buchner et al (1993) found that the dynamic behavior of jet flames was predominantly a function of the Strouhal number. Combustion instability changes the flame length and the flame center length, and therefore the heat release pattern, which affects heat transfer to the chamber walls (Ahn 2014;Kim and Santavicca 2009). A study on the flame length and flame center length in unstable combustion is therefore very important.…”
Section: Introductionmentioning
confidence: 99%